2015
DOI: 10.1177/2158244015580377
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and the Changing Paradigm of Higher Education in the GCC Countries

Abstract: The present study has been undertaken to examine the growth trajectory of the higher education (HE) sector across all the countries in the GCC (Gulf Cooperation Council) region, the transition toward internationalization, quality initiatives undertaken, and movement toward regional integration. The study aims to provide a review for the shifting paradigm through concepts of internationalization in the literature review and to probe on the themes facing the GCC in their adaptation to internationalization. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The explanation for the infrequent mention of technology in the mission statements and course descriptions could fall under one of the following categories: (1) the institutions are in countries such as the Gulf region which find contingencies of the time such as technology, media openness, and knowledge abundance to be challenging (Vardhan 2015); or (2) it is a public university, which is funded mainly by the state, and is therefore tied to the national laws which define the legal framework and institutional goals (World Bank 2012). This may not be a drawback since the core of IaH is the integration of international and intercultural dimensions into curricula, but its presence may be an advanced drive towards internationalization.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for the infrequent mention of technology in the mission statements and course descriptions could fall under one of the following categories: (1) the institutions are in countries such as the Gulf region which find contingencies of the time such as technology, media openness, and knowledge abundance to be challenging (Vardhan 2015); or (2) it is a public university, which is funded mainly by the state, and is therefore tied to the national laws which define the legal framework and institutional goals (World Bank 2012). This may not be a drawback since the core of IaH is the integration of international and intercultural dimensions into curricula, but its presence may be an advanced drive towards internationalization.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that the ABP is unable to achieve the necessary benchmarks of academic readiness for the vast majority of participants to gain acceptance to the American HEIs located in Education City (Mitchell 2013). Furthermore, the UAE and Qatar have not introduced any direct initiatives to improve the quality of their staterun HEIs that enroll the majority of their national students (Vardhan 2015). The fact that there is limited engagement of the national population in these branch campuses raises the question of whether such patterns of HE expansion in Qatar and the UAE serves purposes that are different from that of building a knowledge economy through national human capital development.…”
Section: W or L D S O C I E T Y T H E O R Y E X P A N S I O N A N D I N T E R N A T I O N A L I Z A T I O N O F H I G H E R E D U C A Tmentioning
confidence: 99%
“…Some studies on HE expansion in the Arabian Peninsula have provided a historical analysis, tracing HE developments and reforms in the context of globalization (Donn and Al Manthri 2010;Badry and Wiloughby 2016). Others who have examined HE in the region have either focused specifically on the patterns of internationalization of HE in the Gulf countries (Almarri 2011;Vardhan 2015;Miller-Idriss and Hanauer 2011) or HE development processes of single Gulf countries (Kirk 2010;Khodr 2011). A small number have related HE development to the need for the Arabian Gulf countries to develop a globally competitive knowledge economy for a post-oil era (Miller-Idriss and Hanauer 2011;Badry and Wiloughby 2016).…”
mentioning
confidence: 99%
“…The point of departure in the content of student mobility offers considerable ways of looking at the perpetual differentiation in the role of the institutions worldwide. The recent decade(s) have noted significant change in the functioning of universities under the aegis of globalization-led internationalization of higher education (Vardhan, 2015). The major driver of change is economic globalization, with reduced funding to the universities and institutions at large.…”
Section: Conceptualizing the Process Of Change At The Institutional Lmentioning
confidence: 99%